PELAKSANAAN PUNGUTAN PAJAK SARANG BURUNG WALET OLEH BADAN PENDAPATAN DAERAH KOTA SAMARINDA - Fitri Nurani; Enos Paselle; Tri Susilowati (Program Studi Administrasi Publik Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman, 2021)
East Kalimantan is one of the regions that has the potential for superior non-oil and gas commodities, one of which is swallow’s nest which is currently a leading potential. Tax levies on swallow nest extraction or exploitation activities in Samarinda City have been implemented since 2011. Using a descriptive qualitative type of research, the swallow's nest tax collection implementation by the Regional Revenue Agency of Samarinda City analyzed from the collection and registration of swallow's nest taxpayers, determination of bird's nest tax rates, collection and payment of bird's nest wallet taxes as well as obstacles faced by the Regional Revenue Agency in implementation of swallow's nest tax collection. The results of the research shows that the implementation of swallow's nest tax collection by the Regional Revenue Agency of Samarinda City which refers to the Mayor Regulation Number 27 of 2011 concerning Determination of Rates and Implementation of Swallow's Nest Tax Levies has not been maximized because it still does not meet the standard criteria for implementing tax collection, the less principle of justice in determining swallow's nest tax and there are still many obstacles in implementing swallow's nest tax collection. The obstacles are starting from regulations, understanding of employees, number of employees, employee commitment, field constraints in the data collection process, the potential for swallow's nest, environment, economy, compliance, and compulsory awareness. Taxes are still minimal, up to coordination and cooperation between agencies that handle and are involved in swallow nest business in Samarinda City.